Legal Implications Of Separating National Elections From Local Elections Following Constitutional Court Decision No. 135/Puu-XXII/2024 - Mustiawan; Taufik Firmanto; Ilham (Fakultas Syariah INSURI Ponorogo, 2026)
This article is the result of research examining the legal framework and implications of separating national elections from local elections following Constitutional Court Decision No. 135/PUU/XXII/2024, and identifying an ideal model for that separation. This study is based on the ratio decidendi of Constitutional Court Decision No. 135/PUU-XXII/2024, which separates national elections from local elections, in contrast to Decision No. 55/PUU-XVII/2019, which only offered an alternative model for simultaneous elections. The method used is normative legal research, employing a statutory, conceptual, and case approach. The research findings indicate that, first, Constitutional Court Decision No. 135/PUU-XXII/2024 changes the election design to separate national and local elections, with a time interval of at least 2 years and at most 2 years and 6 months. This arrangement raises legal implications regarding the timing of elections, the synchronization of terms of office, and the limits of the Constitutional Court's constitutional authority. Second, the ideal model for separating elections is a simultaneous national election followed by a simultaneous local election, with an interval of at least 2 years and at most 2 years and 6 months, within a single five-year constitutional cycle. However, its implementation requires legislative harmonization, clear transitional arrangements, and institutional strengthening of election management bodies.